2018
DOI: 10.1080/23293691.2018.1490082
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Related to Prenatal Testing Among Japanese Mothers of Children With Disabilities

Abstract: This study investigated experiences related to prenatal testing among mothers of children with disabilities in Japan. Nearly one third (31.2%) of the mothers gave birth at !35 years, and 16.8% of them underwent prenatal testing. As for mothers of children with Down syndrome, 60.5% of them gave birth at !35 years, and 14.6% of them underwent prenatal testing. Qualitative data also revealed that, even though women 35 years of age or older wanted to undergo amniocentesis, their doctors did not always actively rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…NIPT was introduced in Japan in 2013. There was increase in the total prevalence for prenatal testing from 3% in 2008 to 5.3% in 2013 [31,32]. A total of 44,644 pregnant women underwent NIPT by the end of March 2017 [32] There is no comprehensive policy on prenatal testing and NIPT in Japan.…”
Section: Japanmentioning
confidence: 99%
See 2 more Smart Citations
“…NIPT was introduced in Japan in 2013. There was increase in the total prevalence for prenatal testing from 3% in 2008 to 5.3% in 2013 [31,32]. A total of 44,644 pregnant women underwent NIPT by the end of March 2017 [32] There is no comprehensive policy on prenatal testing and NIPT in Japan.…”
Section: Japanmentioning
confidence: 99%
“…There was increase in the total prevalence for prenatal testing from 3% in 2008 to 5.3% in 2013 [31,32]. A total of 44,644 pregnant women underwent NIPT by the end of March 2017 [32] There is no comprehensive policy on prenatal testing and NIPT in Japan. In addition, NIPT is primarily paid out of pocket by individuals who need it, despite the cost of NIPT in Japan being among the highest in the world [32].…”
Section: Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Hong Kong, NIPT has been integrated into the public health system as a second-tier screening option for highrisk pregnancies (11). In Japan, the introduction of NIPT in 2013 has gradually increased its prevalence in prenatal care, demonstrating the country's evolving approach to maternal and fetal health (12,13). Implementation studies in Japan have shown a significant reduction in invasive procedures, underscoring NIPT's potential to enhance prenatal diagnostic processes while ensuring safety and costeffectiveness (14).…”
Section: Introductionmentioning
confidence: 99%